Four years post-horsegate: an update of measures and actions put in place following the horsemeat incident of 2013. (December 2017) - Brooks, Stephanie; Elliott, Christopher; Spence, Michelle; Walsh, Christine; Dean, Moira
Abstract Complexities in food supply chains were highlighted by the so called 'horsegate' crisis in 2013, where beef meat was fraudulently adulterated with horse meat causing widespread recalls and subsequent investigations across both retail and food service markets in the European Union (EU). The beef supply chain is a complex supply chain, with global (EU and Non EU) sourcing strategies in order to secure supply. However, managing these complex supply chains can be difficult and consequentially can expose vulnerabilities similar to that of horsemeat, where horsemeat was found in beef meat within EU supply chains. Six months after the crisis broke, an independent review into the integrity and assurance of food supply networks was commissioned by the UK government and undertaken by Professor Chris Elliott of Queen's University, Belfast. The review recommended eight pillars of food integrity to industry and government: consumers first, zero tolerance, intelligence gathering, laboratory services, audit, government support, leadership and crisis management. This article examines the extent to which these recommendations have been implemented using personal communications from Professor Chris Elliott and relevant industry bodies. Following the review, industry attitudes have changed substantially, testing and surveillance systems have been integrated into normal industry practice and the government is more prepared for future incidents through the establishment of the National Food Crime Unit (NFCU). Horsegate raised the profile of food fraud and crime in supply chains and despite improvements to date, further collaboration between industry and government is required in order to align fully with the recommendations. Food safety: Food fraud prevention is improved after the 'horsegate' scandal Industry and government have learned their lessons after the incident in 2013 where beef meat was substituted with horsemeat. Using personal communications with representatives of relevant industry bodies, Moira Dean from the Queen's University Belfast in UK and her colleagues examined measures the UK government and food industry have taken in response to the horsemeat scandal. They found significant improvement in the understanding and prevention of food fraud, with well-integrated testing and surveillance systems, along with a new government body to take a leadership role in such crises. Yet, collaboration between industry and government is yet to be enhanced. Given the complexities of international food supply chains, the UK lessons and recommendations to improve the integrity of food supply systems, set out in a review commissioned after the horsemeat crisis are relevant to other countries.